Synthesis of Novel Heterocyclic 4-Thiazolidinone Derivatives and their Antibacterial Activity - K. M. Mistry; K. R. Desai (E-Journal of Chemistry)
4-Thiazolidinones have been prepared by the reaction of various substituted Schiff bases 3 with Thioglycolic acid and Thiolactic acid. The intermediate Schiff bases 3 were synthesized by the condensation of various substituted 2-amino benzothiazole 1 with 1-(4'-methyl Phenyl)-3-methyl-5-pyrazolone 2. The starting compound substituted 2-amino benzothiazoles were prepared from various substituted amines via substituted phenyl thiourea. The structures of the compounds have been confirmed by elemental analysis and spectral analysis. The antibacterial activity of the compounds has also been screened against Staphylococcus aureus and Escherichia coli.